2020
DOI: 10.1136/bmjopen-2019-034627
|View full text |Cite
|
Sign up to set email alerts
|

Association between false positive glucose challenge test results and large-for-gestational-age infants: a retrospective cohort study

Abstract: ObjectivesThere is no consensus regarding a possible relation between false positive glucose challenge test (GCT) results and large-for-gestational-age (LGA) infants. This study aimed to clarify the association between false positive GCT results and LGA, after adjusting for potential confounding factors, using a large clinical dataset.DesignRetrospective cohort study.SettingNational Hospital Organisation Kofu National Hospital, which is a community hospital, between January 2012 and August 2019.ParticipantsJap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…16 In contrast, Shinohara et al suggested that LGA was significantly more common in women having an abnormal GCT but normal OGTT when compared with the GCT normal group. 17 Zhoa et al found that the incidence of macrosomia was significantly greater in Chinese women having abnormal 75-g OGTT values from 1 to 3 time points. 18 Wang observed an increased risk for preterm labor and admission to the NICU when the abnormal value increased in the 100-g OGTT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 In contrast, Shinohara et al suggested that LGA was significantly more common in women having an abnormal GCT but normal OGTT when compared with the GCT normal group. 17 Zhoa et al found that the incidence of macrosomia was significantly greater in Chinese women having abnormal 75-g OGTT values from 1 to 3 time points. 18 Wang observed an increased risk for preterm labor and admission to the NICU when the abnormal value increased in the 100-g OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…Dudhbhai et al reported no different outcomes in macrosomia, cesarean section, preeclampsia, or NICU admission when comparing pregnant women having an abnormal GCT result and a subsequent normal OGTT result with those for whom both test results were normal; therefore, they suggested that women who have an abnormal GCT and subsequent normal OGTT result were at a low‐risk of adverse outcomes 16 . In contrast, Shinohara et al suggested that LGA was significantly more common in women having an abnormal GCT but normal OGTT when compared with the GCT normal group 17 . Zhoa et al found that the incidence of macrosomia was significantly greater in Chinese women having abnormal 75‐g OGTT values from 1 to 3 time points 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While pregnant women have to spend longer periods at the hospital for GCT than those for RPG, if we can create a new strategy such that the pregnant women consume 50 g of glucose for GCT before visiting hospitals, and blood samples are collected 1 hour after consumption, it may shorten the amount of time required for them to be in a hospital. Since pregnant women with false‐positive GCT (ie, positive GCT, but negative OGTT) were at a higher risk of large for gestational age in a previous Japanese report, 5 it might be possible to manage glycemic conditions to false‐positive GCT mothers in the evolving COVID‐19 pandemic.…”
Section: Covid‐19‐gdm Covid‐19‐nft P‐value (N = 104) (N = 160)mentioning
confidence: 98%